Left ventricular function and remodelling in rats exposed stepwise up to extreme chronic intermittent hypoxia - Papoušek, František; Sedmera, David; Neckář, Jan; Ošťádal, Bohuslav; Kolář, František (Respiratory physiology & neurobiology, 2020)
The main aim was to find out whether long-lasting stepwise exposure to extreme hypoxia affects left ventricular (LV) geometry and systolic function. Adult male rats were exposed to intermittent hypobaric hypoxia (8 h/day) with increasing altitude in steps of 1000 m every 3 weeks up to 8000 m. While the LV cavity diastolic diameter did not change over the whole range of hypoxia, the wall thickness increased significantly at the altitude of 8000 m. LV fractional shortening ranged between 48.1 % and 50.1 % and remained unaffected even at the most severe hypoxia. At the end of experiment, haematocrit reached 83 %, mean systemic arterial pressure 120 % and relative LV weight 154 % of normoxic values while RV systolic pressure and relative RV weight doubled. Myocyte hypertrophy and myocardial fibrosis were more pronounced in RV than in LV. In conclusion, LV systolic function was preserved after chronic stepwise exposure of rats to extreme intermittent hypoxia despite moderate concentric hypertrophy and myocardial remodelling.
Keywords: Animals; Hypoxia; Chronic hypoxia; Rats, Wistar; funkce levé komory srdeční; Extreme altitude; Altitude; funkce pravé komory srdeční; Ventricular Remodeling; nadmořská výška; hypoxie; Myocardial remodelling; Ventricular Function, Right; Male; remodelace komor; krysa rodu Rattus; Heart function; mužské pohlaví; zvířata; Rats; Ventricular Function, Left; potkani Wistar